SNACK BAR MADE FROM SORGHUM AND BEANS WITH ADDITION OF RED PALM OIL AS SUPPLEMENTARY FOOD FOR PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY - Aisyah Nurhusna; Sri Anna Marliyati; Eny Palupi (Media Gizi Indonesia, 2020)
The prevalence of chronic energy defi ciency in pregnant women was in poor conditions since 2016 to 2018. One of the solution to overcome chronic energy defi ciency in pregnant women is by providing supplementary food as snack, such as snack bar. Snack bar was made from sorghum and beans (red bean and black soybean) which are local food source of energy and protein. The objective of this study was to develop and analyze sorghum and beans-based snack bar with addition of red palm oil (RPO) as supplementary food for pregnant women with chronic energy defi ciency. This study used complete randomized design with the ratio of sorghum fl akes and beans chunks with the addition of RPO as treatment in three replications. Determination of selected formula were based on sensory analysis and protein content of product. The selected formula was F4 (ratio of sorghum fl akes:beans = 2:1, 2% RPO) which contained 8.59% moisture, 2.38% ash, 15.26% protein, 21.38% fat, 3.67% crude fi ber, 52.05% carbohydrates, 447 kcal energy, 10.98% dietary fi ber, 27,35 mg/kg β-carotene, 23.00 mg/kg iron, 13.21 mg/kg zink, 304.40 mg/kg calcium, 48.69% the limiting amino acid score, and 75.84% protein digestibility. F4 could be accepted by pregnant women with overall acceptability of 97%. F4 potentially be used as one of the alternative supplementary food for pregnant women with chronic energy defi ciency because of its acceptability, enable to fulfi ll supplementary food standard, and had higher protein and fi ber content than existing supplementary food for pregnant women with chronic energy defi ciency